Studies of Some Bismuth Based Electrolytes for Solid Oxide Fuel Cells - Kant, Ravi (My University, 2008)
Ionic conductivity is the result of ions migration. It pays a key role in the development of electrolyte materials for several electrochemical devices like solid oxide fuel cell (SOFC). Solid electrolytes are the class of materials found to exhibit high ionic conductivity which depends upon different transport mechanism associated with it. Other type of conduction e.g. electrons (electronic conductivity) reduces the efficiency of solid oxide fuel cell due to internal short circuit. Oxide phases derived from Bi2O3 are particularly interesting due to their high ionic conductivity with respect to other solid electrolytes. High conducting δ-phase of Bi2O3 can be stabilized down to room temperatures by the substitution with V2O5 thus forming Bi4V2O11 compound. Materials like yittria stabilized zirconia (YSZ), La10-xGe6O26.5 etc. require high temperatures for their synthesis. Their compatibility and performance with other components of devices show limited applicability. The cost and maintenance of a fuel cell stack makes it mandatory to operate it below 800oC, but these temperatures are at the technical limit that can not be achieved with YSZ as the electrolyte below 800 oC. Moreover, oxygen ion conduction through the YSZ electrolyte membrane is a highly activated process, thus resulting in high voltage losses across the layer at lower temperatures. This fact continues to motivate to search for developing electrolytes with low resistance at intermediate temperatures. Currently, considerable attention is paid to search solid oxide electrolyte materials which exhibit high ionic conductivity at low temperature. Replacement of YSZ with intermediate temperature oxide ion conductor in solid oxide fuel cell would give a significant reduction in the material cost and fabrication problems together with an v improvement in the efficiency and longevity of the cell. Solid solutions based on γ- Bi4V2O11 by partial substitution of vanadium with metal cations (Bi4V2-xMexO11) exhibit high ionic conductivity and oxygen ion transference numbers close to unity at temperatures below 600oC. Although, these materials were developed as early as 1986 when Bush and Debreuille-Gresse reported some of the highest oxygen-ion conductivities to date. Since then a large number of systems were developed and investigated. In order to demonstrate the superiority of the bismuth vanadate based compounds as compared to the other commonly used materials, a number of new electrolytes doped on the vanadum and bismuth sites respectively were prepared: (i) Bi4V2-xMexO11-δ (Μe = Cu2+, Mn2+, Ti3+, Al3+, Cr3+, Ga3+ and As5+) (ii) Bi4-xV2MexO11-δ (Μe = Pb2+, La3+ and Gd3+) and their physical and electrical characterizations were carried out in the present work. In all the systems, the composition selected is x = 0.1, 0.2, 0.3, 0.4 and microstructural study was carried out to correlate it with the ionic conductivity. This was undertaken because of fact that no systematic study up to higher composition range and its correlation with microstructure is reported in the literature.
Keywords: Fuel Cell; Ceramics